Peduli Cegah Stunting Pada Anak di Kota Palangka Raya - Marhaeni Fajar Kurniati; Husen Arif Hidayat; Dessy Angreni; Deby Nuriadini; Ahsanu Amalaa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Recently, stunting has been hotly discussed by many people, especially mothers. According to WHO, stunting is a child's growth and development disorder caused by a lack of nutritional intake, infection, or inadequate stimulation. The number of stunting sufferers in Indonesia according to the 2018 Riskesdas results continues to decline. Community service activities for UNISKA MAB Banjarmasin students with the theme